Students’ Ability in Pronouncing English Words by Using ELSA Speak Application of the Second-Year Students of SMA Eka Prasetya Medan - Sahlan Tampubolon; Dameasi Bulan P Lumban Gaol; Nenni Triana Sinaga; Sanggam P Gultom (Universitas Pahlawan Tuanku Tambusai, 2023)
Pronunciation is one of difficult to learn. There are particular problems occur in much pronunciation teaching and learning. The first, a lot of students can’t do the challenging about the pronunciation clue. The second, every students have the capacity to produce the sounds since the baby. The third, the intonation is the most difficult aspect of pronunciation for many students. Elsa Speak Application is the application that can help the users to improve pronunciation. This study aims to describe the students’ ability in pronouncing English words by using ELSA Speak Application of the second-year students of SMA Eka Prasetya Medan. Methodology used in this study descriptive qualitative, field research, library research. Instrument used collecting the data test, recording, and transcribing. Findings are, students’ ability in pronouncing English words who the students able, less able or unable. From ten students, they were still lack when pronounce the English words such as words “Creator”, “Drunk” , “Together” they pronounced this word wrong from ten students. Based on the data, the writer found that 2 students that can be able pronounced the words well. Students 4, 25 words able (83,3%), and 5 words almost correct (16,6%). Students 7, 22 words able (73,3%), and 8 words almost correct (26,6%).